Android-based multi-IoT fish feeding system: An end-to-end information system approach - Adyatma, Putu Nanda Arya; Buana, Putu Wira; Suarjaya, I Made Agus Dwi (Matrix : Jurnal Manajemen Teknologi dan Informatika, 2025)
The ornamental fish industry in Indonesia has experienced significant growth, positioning the country as the second-largest global exporter of ornamental fish in 2020. However, fish shop owners still face operational challenges, especially in managing consistent and timely feeding across multiple aquariums. Manual feeding practices often lead to inefficiencies and can compromise fish health and water quality. This study presents an end-to-end fish feeding information system integrated with an Android mobile application, designed to address these challenges. System development in this study employs waterfall method. The system supports automated fish feeding routines, device management, and multi-user access with token-based authentication, enabling fish shop owners to operate multiple feeders under a single account. Communication between IoT devices and the backend server utilizes MQTT, ensuring independent control of each feeder through unique topics. The system introduces a novel architecture that supports multi-user, multi-device operations in an end-to-end feeding workflow, improving scalability and efficiency compared to existing single-device systems. System testing, including black box and load testing, demonstrated robust performance, with all test scenarios passing successfully and an error rate of 0.00% during high-load simulations involving up to 100 virtual users. These results indicate that the system effectively addresses existing limitations in fish feeding management and is capable of supporting multiple users and fish feeder devices simultaneously. Further development is recommended to enhance infrastructure, security, and scalability for real-world deployment.